Impact of Repository Size on SpikingBrain and Llama 2 13B Pass-at-One Performance - Assignee Research (Assignee Research, 2026)
This report synthesises findings from 13 peer-reviewed papers addressing the following research question: What is the impact of repository size (measured in lines of code) on the pass@1 scores of SpikingBrain versus Llama 2 13B when benchmarked on multi-file repository-level coding tasks. 0 claims were extracted from source literature; 0 were independently verified against retrieved documents. An automated multi-reviewer quality assessment produced a score of 3.7/10. This report is a machine-gen
Machine-generated literature synthesis.